Stability of positive and monotone systems in a partially ordered space - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate properties of positive and monotone dynamical systems with respect to given cones in the phase space. Stability conditions for linear and nonlinear differential systems in a partially ordered space are formulated. Conditions for the positivity of dynamical systems with respect to the Minkowski cone are established. By using the comparison method, we solve the problem of the robust stability of a family of systems.